Perceived Value of Teaching and Learning Curriculum Programs Among Pharmacy Practice Department Chairs - Beckett, Robert D. (Am J Pharm Educ, 2020)
Objective. To determine the perceived value that pharmacy practice department chairs ascribe to pharmacy faculty candidates having completed a teaching and learning curriculum (TLC) program and related activities. Methods. An 18-item survey instrument was created that was intended to capture the overall impressions of pharmacy practice chairs regarding the value of TLC programs, relative importance compared to other accomplishments (eg, residency completion, board certification), and importance of specific activities. Following pilot testing and establishment of intra-rater reliability, invitations to complete the electronic survey instrument were sent to pharmacy practice chairs (or their equivalent) at accredited Doctor of Pharmacy (PharmD) programs in the United States. Results. Of the 127 pharmacy practice chairs invited, 53 completed the survey (response rate of 41.7%). The majority of respondents held a PharmD degree (90.6%), had been in their role of chair for zero to five years (60.4%), and represented a private institution (54.7%). The majority of respondents who answered the question (32 of 49) felt it was very important or important (16.3% and 49.0%, respectively) that teaching experiences be completed within a formal teaching and learning curriculum program. These programs were believed to be most important for candidates with less than five years of professional experience. Teaching and learning curriculum programs were not deemed to be more important than other accomplishments by most responders. The perceived most important TLC program activities were instruction on didactic and experiential teaching strategies, and experience developing learning objectives, developing examination items, evaluating examination results, and facilitating case conferences or practice laboratory activities. Conclusion. Teaching and learning curriculum programs may provide the foundational experiences needed for pharmacy graduates to stand out among other candidates, although department chairs’ perceptions of the value of teaching and learning curriculum experiences varied.